Diffusion-Weighted Magnetic Resonance Application in Response Prediction before, during, and after Neoadjuvant Radiochemotherapy in Primary Rectal Cancer Carcinoma. (10th July 2013) - Musio, Daniela; De Felice, Francesca; Magnante, Anna Lisa; Ciolina, Maria; De Cecco, Carlo Nicola; Rengo, Marco; Redler, Adriano; Laghi, Andrea; Raffetto, Nicola; Tombolini, Vincenzo
Abstract : Introduction . Our interest was to monitor treatment response using ADC value to predict response of rectal tumour to preoperative radiochemotherapy. Materials and Methods . Twenty-two patients were treated with long course of radiochemotherapy, followed by surgery. Patients were examined by diffusion-weighted imaging MRI at three-time points (prior, during, and after radiochemotherapy) and were classified as responders and nonresponders. Results . A statistical significant correlation was found between preradiochemotherapy ADC values and during treatment ADC values, in responders (F = 21.50, P value < 0.05 ). An increase in ADC value during treatment was predictive of at least a partial response. Discussion . Response of tumour to neoadjuvant therapy cannot be easily evaluated, and such capability might be of great importance in clinical practice, because the number of irradiated and operated patients may be superior to the number of who will really benefit from this multimodal treatment. A reliable prediction of the final clinical TN stage would allow radiotherapist to adapt multidisciplinary approach to a less invasive management, sparing surgical procedure in responder patients or even allowing an early surgery in nonresponders, which would significantly reduce radiochemotherapy related toxicity. Conclusion . Early evaluation of response during neoadjuvant radiochemotherapy treatment shows great promise to predict tumour response.